Kewenangan Mahkamah Konstitusi Dalam Menangani Perkara Perselisihan Hasil Pemilihan Umum 2024 - Christine S.T Kansil; Namira Diffany Nuzan (UNES Law Review, 2024)
The writing of this research is based on the aim that an assessment will be carried out regarding the extent of the authority of the constitutional court in handling the 2024 election dispute case submitted by the presidential candidate pair and also the vice presidential candidate in serial number 3 and serial number 1. The basis for submitting the petition to the constitutional court by of the candidate pair that there are indications that there was a massive structured and systematic act of fraud in the 2024 election carried out by presidential and vice presidential candidate number 2 where in the implementation of this year's election the principles of fairness and overflow were not implemented properly. Therefore, a problem that can be studied is whether the constitutional court has the authority to handle this case, as in accordance with Law Number 24 of 2003 which regulates the authority of the constitutional court in Article 10 paragraph 1 letter a. Therefore, in the implementation or results of this research, the author really hopes that it will be useful for the constitutional court and the parties involved in this matter. Apart from that, readers will also be able to find out about the extent of authority that the constitutional court has in handling disputes over election results.